RELIGION, MARGINALITY AND POWER RELATIONS: RELIGIOUS CONVERSION AND RELIGIOSITY OF THE INDIGENOUS PEOPLE IN PENYENGAT - Muhammad Ansor; Laila Sari Masyhur (Graduate Program of Pontianak Institute of Islamic Studies, 2013)
Using a theory of power relation of Michel Foucault, the following research analyzes the behavior of religious conversion in the community of the Indigenous People of Anak Rawa in Penyengat Village, Siak District, hereinafter referred to as the Native People. The research will show that in the middle of the domination of the State and theologians, the community of Indigenous People actualizes power to maintain its identity in the midst of the invasion of new values and culture. To support the argument, the researchers traced the religiosity of the Indigenous People focusing on several events of everyday life such as traditions of marriage, death, and celebration of religious holidays. In addition to adapting to the country’s religious traditions they have adopted, this community also modifies the ritual traditions of each religion so that these traditions become a means of preserving their communal identity as a native tribe. The research ultimately shows the interplay between the State and theologians as the dominant group, on the one hand, and the indigenous community as a subjugated group, on the other, in the use of power. Keywords: Indigenous People, Religion, Power Relation